2018
DOI: 10.1021/acs.chemmater.8b00903
|View full text |Cite
|
Sign up to set email alerts
|

Size and Concentration Determination of Colloidal Nanocrystals by Small-Angle X-ray Scattering

Abstract: The accurate determination of the dimensions of a nano-object is paramount to the de-velopment of nanoscience and technology. Here, we provide procedures for sizing quasi-spherical colloidal nanocrystals (NCs) by means of small-angle x-ray scattering (SAXS). Using PbS NCs as a model system, the protocols outline the extraction of the net NC SAXS pattern by background correction and address the calibration of scattered x-ray intensity to an absolute scale. Different data analysis methods are compared, and we sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(147 citation statements)
references
References 44 publications
4
127
0
Order By: Relevance
“…The optical band gap of the CdSe and PbS nanocrystals were determined by UV-VIS-NIR absorption spectroscopy (Perkin Elmer Lambda 900) and correlated to a nanocrystal diameter by aid of sizing curves that were recently re-evaluated by SAXS. 53 Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) were performed on a FEI Talos Bruker Avance III Spectrometer operating at a 1 H frequency of 500.13 MHz and featuring a BBI probe. The sample temperature was set to 298.15 K. For the quantitative 1D 1 H measurements, 64k data points were sampled with the spectral width set to 16 ppm and a relaxation delay of 30s.…”
Section: Characterizationmentioning
confidence: 99%
“…The optical band gap of the CdSe and PbS nanocrystals were determined by UV-VIS-NIR absorption spectroscopy (Perkin Elmer Lambda 900) and correlated to a nanocrystal diameter by aid of sizing curves that were recently re-evaluated by SAXS. 53 Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) were performed on a FEI Talos Bruker Avance III Spectrometer operating at a 1 H frequency of 500.13 MHz and featuring a BBI probe. The sample temperature was set to 298.15 K. For the quantitative 1D 1 H measurements, 64k data points were sampled with the spectral width set to 16 ppm and a relaxation delay of 30s.…”
Section: Characterizationmentioning
confidence: 99%
“…SAXS is a powerful technique to characterize the structures of large synthetic molecules, molecular assemblies, nanoparticles 34 and aggregates with sizes ranging from 1 to 100 nm. 35,36 With regard to POM chemistry, we and others have shown that this technique is particularly well-suited to characterize nanosized metal-oxo cluster assemblies.…”
Section: Formation and Characterization Of Discrete Molecular Dumbbellsmentioning
confidence: 99%
“…Characterization techniques used thus far to investigate the surface properties of NCs include X-ray photoelectron spectroscopy [45,46], UV-vis spectroscopy [47], infrared spectroscopy [48], photoluminescence spectroscopy [49][50][51], and nuclear magnetic resonance (NMR) spectroscopy [52,53]. To determine the properties of surface ligands or the interfacial properties between organic and inorganic elements, various characterization techniques must be combined [54].…”
Section: Characterizationmentioning
confidence: 99%
“…Several researchers have reported a correlation between the first absorption peak of semiconducting QDs (e.g., CdS, CdSe, PbTe, PbSe, and CdTe) and their size. Peng et al summarized these values and suggested empirical fitting functions [40,46,47]. These equations are only valid in the size range covered by the data shown in Figure 6 [47].…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation